Macbeth - Shakespeare, William, 1564-1616; Crowther, John (New York : Spark Publishing, 2003)
Presents the original text of Shakespeare's play side by side with a modern version, with marginal notes and explanations and full descriptions of each character.
Keywords: Shakespeare, William, -- 1564-1616. -- Macbeth; Macbeth, King of Scotland -- 11th century -- Drama; Scotland -- Kings and rulers -- Drama